Improving the ability to understand mathematical concepts and achievement of self-determination of elementary school students using realistic mathematics education approach - Samura, Asri Ode; Siagian, Muhammad Daut (Journal of Didactic Mathematics, 2023)
This study examines the differences in the increase in the ability to understand mathematical concepts and the achievement of students' self-determination using the RME approach. Quantitative research method by way of the experiment using "nonequivalent control-group design." The research sample amounted to 81 people. The instrument used is in the form of an essay test. Data obtained from the pretest and posttest were analyzed using descriptive and inferential statistics. The results obtained; The RME technique has a very high impact on the category's ability to comprehend mathematical ideas and attain self-determination. The RME method can help primary school children gain self-determination and increase their understanding of mathematical ideas. Students who learn to use the RME technique and students who learn to use conventional learning have different increases in their capacity to understand mathematical topics. There is no difference in self-determination between students who learn to use the RME approach and those who use conventional learning.